PEMBUATAN PETA CITRA DESA TOYAREKA SKALA 1:5.000 BERBASIS GOOGLE EARTH PRO - Wafdan, Labisa (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
Abstract The village map is basic geospatial information about the appearance of natural and thematic elements of a village which is presented in a map to be used as a basis for spatial planning in the growing land uses. To accelerate the availability of village maps, a participatory mapping method was carried out so the community could determine the acquisition and utilization of mapping data according to their own needs. Through this research, Toyareka Village became one of the areas that were mapped using Google Earth Pro's very high-resolution image and remote sensing technique. This research method through the two steps i.e. the preparation and presentation steps. The Delineation step involves collecting various data processes about the map elements from the field observation and the interview process with the village government. The map elements which were obtained are toponymy; village boundary; transportation network/infrastructure; waters (rivers); along with the facilities and infrastructure (public facilities and social facilities). The presentation step is the unification of the Toyareka Village image and the results of map elements that were depicted on a map sheet. The result of this study is a map of Toyareka Village which was made following the Head Regulation of Geospatial Information Board Number 3 of 2016 concerning technical specifications for the presentation of village maps. This map will be submitted to the community of Toyareka Village through the village government, so the community can find out and use the map information according to their needs. Abstrak Peta desa merupakan informasi geospasial dasar mengenai kenampakan unsur-unsur alam dan unsur tematik suatu desa yang disajikan dalam sebuah peta untuk digunakan sebagai dasar perencanaan tata ruang dalam pemanfaatan lahan yang terus berkembang. Untuk mempercepat ketersediaan peta desa tersebut, metode pemetaan partisipatif dilakukan sehingga masyarakat bisa menentukan proses akuisisi dan penggunaan data hasil pemetaan sesuai kebutuhan mereka sendiri. Melalui penelitian ini, Desa Toyareka menjadi salah satu daerah yang dipetakan menggunakan teknik penginderaan jauh berbasis citra resolusi sangat tinggi dari Google Earth Pro. Metode penelitian ini melalui dua tahap, yaitu tahapan persiapan dan penyajian. Tahapan persiapan melibatkan proses pengumpulan berbagai data unsur peta yang diperoleh dari pengamatan langsung di lapangan beserta wawancara dengan aparatur pemerintahan desa. Unsur-unsur peta yang diperoleh adalah toponimi; batas wilayah desa; jaringan/infrastruktur transportasi; perairan (sungai); beserta sarana dan prasarana (fasilitas umum dan fasilitas sosial). Tahapan penyajian merupakan penyatuan data citra Desa Toyareka dan hasil pengumpulan data unsur-unsur peta yang digambarkan pada sebuah lembar peta. Hasil penelitian ini berupa peta Desa Toyareka di buat sesuai dengan Peraturan Kepala Badan Informasi Geospasial No. 3 Tahun 2016 tentang Spesifikasi Teknis Penyajian Peta Desa. Peta ini akan diserahkan kepada masyarakat Desa Toyareka melalui pemerintah desa, sehingga masyarakat dapat mengetahui dan menggunakan informasi peta desa sesuai kebutuhan mereka.